Selection and reliability of financial ratios in an attempt to analyse financial statements. An empirical research of the listed companies at Greek stock exchange in Construction Sector. Dimitrios Tsiolis MA Finance - Tsiolis, Dimitrios (2008)
Financial ratio analysis is a widely known financial statements analysis tool and is used to evaluate companies` financial position. Careful selection process in collaboration with other financial statement analysis techniques as well as taking into consideration the financial ratio analysis problems can lead the companies' analysts to a clear determination of their company's financial position.